Assessing perceptions of nursing knowledge, attitudes, and practices in diabetes management within Chinese healthcare settings - Hu, Lan; Jiang, Wen (Frontiers in Public Health, 2024)
Background Effective management of diabetes mellitus (DM) involves comprehensive knowledge, attitudes, and practices (KAP) by nurses, which is essential for optimal patient care and aiding patients in their self-management of the condition. Method This survey evaluates nurses' self-assessed knowledge, attitudes, and practices (KAP) related to diabetes management, focusing on their perceptions of personnel expertise and care approaches. Using a stratified sampling method, the survey was disseminated across various online platforms from January 2023 to February 2024 within China, including WeChat and Sina Weibo. We employed binary logistic regression and Chi-square tests to explore the statistical correlates of KAP related to DM. Results A total of 4,011 nurses participated, revealing significant perceived knowledge deficiencies in specialized DM management areas, with only 34% (n = 1,360) proficient in current pharmacological treatments. Attitudinal assessments showed that 54% (n = 2,155) recognized the importance of cultural competence in dietary counseling. Practices were strong in routine glucose monitoring (96%, n = 3,851) but weaker in psychological support (68%, n = 2,736). Regression analysis indicated significant effects of experience on KAP, where nurses with 1–5 years of experience were more likely to show better knowledge (OR = 1.09; p = 0.08), and those with advanced degrees demonstrated higher competence (OR = 1.52; p = 0.028). Marital status influenced attitudes, with single nurses more likely to exhibit positive attitudes (OR = 0.49; p < 0.001), and work environment impacted knowledge, with hospital-based nurses more knowledgeable (OR = 1.15; p = 0.14). Additionally, gender differences emerged, with male nurses showing greater knowledge (OR = 1.65; p = 0.03) and better practices in diabetes care (OR = 1.47; p = 0.04). Conclusion The study underscores the critical need for targeted educational programs and policy interventions to enhance nursing competencies in DM management. While the study provides valuable insights into nurses' perceptions of their competencies, future research should incorporate objective knowledge assessments to ensure a comprehensive understanding of their actual capabilities. Interestingly, the data also suggests a substantial opportunity to leverage technology and inter-professional collaboration to further enhance DM management efficacy among nurses, fostering an integrated care approach.